2000
DOI: 10.1074/jbc.275.2.1300
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Protein Encoded by the Hermansky-Pudlak Syndrome Type 1 Gene

Abstract: Hermansky-Pudlak syndrome (HPS) comprises a group of genetic disorders characterized by defective lysosome-related organelles. The most common form of HPS (HPS type 1) is caused by mutations in a gene encoding a protein with no homology to any other known protein. Here we report the identification and biochemical characterization of this gene product, termed HPS1p. Endogenous HPS1p was detected in a wide variety of human cell lines and exhibited an electrophoretic mobility corresponding to a protein of ϳ80 kDa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
90
2
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 35 publications
10
90
2
1
Order By: Relevance
“…5B) allowed us to estimate sedimentation coefficients within the ranges of 5.9-6.8 S and 5.3-6.6 S for BLOC-3 from HeLa and MNT-1 cells, respectively. These sedimentation coefficient values were in close agreement with those previously reported for BLOC-3 [45,46,52]. Owing to the extent of overlap in these value ranges, we suspect that the molecular composition of BLOC-3 may be identical in both pigmented and non-pigmented cells.…”
Section: Does Human Bloc-3 Contain Additional Subunits?supporting
confidence: 81%
See 2 more Smart Citations
“…5B) allowed us to estimate sedimentation coefficients within the ranges of 5.9-6.8 S and 5.3-6.6 S for BLOC-3 from HeLa and MNT-1 cells, respectively. These sedimentation coefficient values were in close agreement with those previously reported for BLOC-3 [45,46,52]. Owing to the extent of overlap in these value ranges, we suspect that the molecular composition of BLOC-3 may be identical in both pigmented and non-pigmented cells.…”
Section: Does Human Bloc-3 Contain Additional Subunits?supporting
confidence: 81%
“…Although we had previously raised a number of rabbit polyclonal antibodies against almost all BLOC subunits [17,42,45,46,50], preference was given to mAbs since they can be obtained from propagative sources (i.e., hybridomas).…”
Section: Specificity and Sensitivity Of Antibodies To Representative mentioning
confidence: 99%
See 1 more Smart Citation
“…HPS1 and HPS4 are the only types of HPS that present with lung fibrosis, a symptom that often leads to mortality in the fourth or fifth decade of life (2). Although the most visible manifestations of HPS1 or HPS4 deficiency derive from LRO defects, both proteins are expressed in all cell types, including those that normally lack LROs (11,13,14). Human HPS1 has 700 amino acids and a predicted molecular mass of 79 kDa (11), whereas human HPS4 has 708 amino acids and a predicted molecular mass of 77 kDa (14).…”
mentioning
confidence: 99%
“…Furthermore, in culture cells derived from patients with HPS2 gene mutation, CD1b failed to efficiently gain access to lysosomes, resulting in a profound defect in antigen presentation (23) while another human fibroblast with HPS2 mutation caused complete deficiency of adaptor complex-3 protein and increased protein trafficking through LAMP-3 with upregulation of antigen-presenting capacity (14,22 1F ATGGAAGTCCCTTGTGATGC 10F CAATGGGTGGGTCCAACTTA 1R CAGGTTTTCCTGCCTCTCTG 10R ATGGAGAAGCCATCCATCAG 2F TCTGGCCCACTCTAAGCTGT 11F AGGAAAGCTACTGCCCCCTA 2R CATCAAGCTGAGGGAAGAGG 11R GGAAAACAAGGATCGTAGGC 3F AAGGCAGAAACGGCATCTA 12F AGAAGGACTTTGGCCTGGAC 3R AAAATGGCAGCTTCACAGG 12R ATCAGGCAATGGGAAGGAG 4F GGGAGACCAGCTTTCTTGTG 13F AGGTTGGTCTGTCCTGGGTA 5F GAAGGTTTCAGGCTTCATGG 13R ACCAGCAAGAAGTCCTTCCA 5R GGGACCTGGTGGGTCTTAGT 14F CCATCTACCGGCTGAACTTT 6F GTATTTGTGCCTTGCCCATC 14R CCTTCAGAGAGGTGGTGAGC 6R CACCATCTTCAGGCAGGTTT 15F CTGGGGAGCTTGGAGGTAGT 7F ATCGAATCCCTGGGAAGTCT 16F GAGGGTAGTCCATCCATCCA 7R ACTCCTCAGGGAGGGAGAAG 16R TACAGAGCGGGAACTGTGTG 8F GTGTGTGCTGTGCACTTCGT 17F AACAAGGTCCAGCATTTTC 8R AGACAGCGTCCTGTGCTCTA 17R GGAACACAGATGTACCCTCCA 9F TTAGGATGAAGGGGTGTTGC 18F CCAGGATGCCACTGTTAGGT 9R TCAGAGCCCCCAATACTCAC 18R GGTGGTCTAGGTGGGGTTTT had a history of recurrent bacterial infection in the lungs. It is apparent that the proteins encoded by the HPS gene have multiple effects on the immune system (14,22,24). Harmon et al reported that macrophage-derived peptides are important candidate molecules in the initiation of alveolar remodeling in fibrotic lung disorders (25).…”
Section: Discussionmentioning
confidence: 99%